2006
DOI: 10.1248/cpb.54.409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decrease in Both Postprandial Blood Glucose (PBG) and Fasting Blood Glucose (FBG) Levels in Normal Beagle Dogs with Nateglinide Enteric Coated Granules and Immediate Release Tablets

Abstract: Ordinary antidiabetics for oral administration are classified into two types. The first type primarily controls postprandial blood glucose level (PBG), while the other type primarily controls fasting blood glucose level (FBG). 1,2) There is currently no oral antidiabetic capable of controlling both PBG and FBG, and such an antidiabetic is believed to be the most useful for the treatment of diabetes.The D-phenylalanine derivative, nateglinide ((Ϫ)-N-(trans-4-isopropylcyclohexanecarbonyl)-D-phenylalanine) was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…Therefore, nateglinide In order to decrease FBG with nateglinide, it is necessary to conduct a sustained release of nateglinide. 4) When administering enteric coated granules with meal, it was reported that a sustained release of the drug was achieved. 4,[6][7][8][9][10] Moreover, it was reported that nateglinide was only partially absorbed in the stomach, but was well absorbed in the whole area of the intestines, according to the in situ experiment in rats using a ligated loop method.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, nateglinide In order to decrease FBG with nateglinide, it is necessary to conduct a sustained release of nateglinide. 4) When administering enteric coated granules with meal, it was reported that a sustained release of the drug was achieved. 4,[6][7][8][9][10] Moreover, it was reported that nateglinide was only partially absorbed in the stomach, but was well absorbed in the whole area of the intestines, according to the in situ experiment in rats using a ligated loop method.…”
Section: Resultsmentioning
confidence: 99%
“…It was thought to be necessary to coat 15 w/w% or more of enteric coating material on core granules to obtain acid resistance. 4) Therefore, 15 w/w% or more of enteric coating materials were coated on the core granules (Enteric Coated Granules (a): 22 w/w% of methacrylic acid copolymer LD (Eudragit ® L30D-55), Enteric Coated Granules (b): 31.4 w/w% of methacrylic acid copolymer LDϩpoly(methyl acrylate-co-methyl methacrylate-co-methacrylic acid) (Eudragit ® FS30D) (1 : 9 dry substance weight ratio), Enteric Coated Granules (c): 31.6 w/w% of poly(methyl acrylate-co-methyl methacrylate-co-methacrylic acid)). The loss on drying values were 3.6 w/w% (Enteric Coated Granules (a)), 3.4 w/w% (Enteric Coated Granules (b)), 3.2 w/w% (Enteric Coated Granules (c)) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations